Dampak Profitabilitas, Suku Bunga, dan Tingkat Pengembalian yang Diharapkan terhadap Efektifitas Penganggaran Modal (Perusahaan Gas Industri Periode 2018-2022 ) - Siti Nur Azizah; Nensi Rahma Nor Hakiki; Sarah Sarah; Firstya Trista Faradiba; Maria Yovita R. Pandin (BADAN PENERBIT STIEPARI PRESS, 2025)
The purpose of this study is to examine and analyze the extent to which profitability, interest rates, and expected returns influence the effectiveness of capital budgeting in industrial gas companies listed on the Indonesia Stock Exchange (IDX) during the 2018–2022 period. Capital budgeting is an essential tool for determining the feasibility of long-term investments through the evaluation of expected financial benefits. This research employs a quantitative method using multiple linear regression analysis to measure the relationship among variables. The results show that profitability, as measured by Return on Assets (ROA), has a positive and significant effect on improving the effectiveness of capital budgeting. In contrast to profitability, interest rates have a negative and significant impact. Meanwhile, expected returns also have a positive effect, but the influence is not statistically significant. These findings emphasize the importance for company management to consider both internal and external financial factors in investment planning to create sustainable added value.